2012
DOI: 10.1055/s-0032-1329920
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Analysis of the Role of Plastic Surgery in Extremity Sarcoma Treatment

Abstract: Over the past 5 years we have developed a multidisciplinary service for the treatment of extremity sarcoma. This service includes orthopedic oncology, neurosurgery, medical and radiation oncology, and plastic surgery. Prior to 2007, the role of plastic surgery in this multidisciplinary team was limited. After 2007, plastic surgery at our institution played an increasingly integral role in multidisciplinary care. Based on the development of the plastic surgery service at our institution, we were able to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 8 publications
(8 reference statements)
0
29
0
Order By: Relevance
“…In theory, flap reconstruction after STS resection and radiation should decrease perioperative morbidity rates. Matching results were described in some studies showing increased morbidity rates in patients treated with direct closure rather than vascularised flap reconstruction . O'Sullivan et al found that complication rates after direct closure were 15%, compared to 2% with additional vascularised tissue transfer.…”
Section: Complications Of Radiotherapy With Free Flaps Compared To Prmentioning
confidence: 73%
See 4 more Smart Citations
“…In theory, flap reconstruction after STS resection and radiation should decrease perioperative morbidity rates. Matching results were described in some studies showing increased morbidity rates in patients treated with direct closure rather than vascularised flap reconstruction . O'Sullivan et al found that complication rates after direct closure were 15%, compared to 2% with additional vascularised tissue transfer.…”
Section: Complications Of Radiotherapy With Free Flaps Compared To Prmentioning
confidence: 73%
“…The mean total dose in the reviewed literature was relatively homogenous and ranged from 50 to 70 Gray (Gy), with details shown in Table . It was not mentioned in six studies . The fractionation of the radiotherapy dose was either 1.8 or 2 Gy as shown in Table .…”
Section: Complications Of Radiotherapy With Free Flaps Compared To Prmentioning
confidence: 99%
See 3 more Smart Citations